Thin film PZT-Si structure with quadrant-diagonal electrode system as an element of position sensitive pyroelectric detector - Bravina, S.L.; Cattan, E.; Morozovsky, N.V.; Remiens, D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The main characteristics of position sensitive systems of pyroelectric detectors of radiation (PDR) with sensitive elements based on PZT film on Si-substrate were investigated by photopyromodulation method. Pt-PZT-Pt/Ti-SiO₂/Si structures with 1.9 mm (111)-oriented PZT (54/46) layer were manufactured by R.F. magnetron sputtering. Top Pt electrodes in a shape of isosceles rectangular triangle together make the quadrant-diagonal system. The results of pyroelectric undersurface probing and “along surface” pyroelectric scanning show that the investigated quadrant-diagonal system of SE makes it possible to examine all main types of differential position-sensitive PDR. The experimental results for investigated 2-element single-coordinate PDR variants are in a good agreement with calculations for the corresponding systems.